2016
DOI: 10.1021/acssuschemeng.6b01010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Quinolines: A Green Perspective

Abstract: The quinoline scaffold is present in a vast number of natural compounds and pharmacologically active substances, comprising a significant segment of the pharmaceutical market. The classical methods for the synthesis of this heterocyclic skeleton require the use of expensive starting materials and high temperature conditions. Chemists play a fundamental role in the construction of a sustainable future through the pursuit of greener chemical processes. As so, the development of new synthetic methods using more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 106 publications
0
33
0
Order By: Relevance
“…Quinolines can be synthesized using a number of classical methods including the Friedländer, Skraup, Combes, and Doebner–von Miller syntheses from anilines and carbonyl compounds, as well as metal-catalyzed dehydrogenative cyclization and other “greener” methods [ 14 , 15 , 16 , 17 ]. In the current work, quinolines 5a – 5f , 6a – 6f and 7a – 7g were synthesized using the Friedländer method by condensation of the corresponding 2-aminobenzaldehydes, prepared from substituted 2-nitrobenzaldehydes [ 18 ], with aldehydes or ketones.…”
Section: Resultsmentioning
confidence: 99%
“…Quinolines can be synthesized using a number of classical methods including the Friedländer, Skraup, Combes, and Doebner–von Miller syntheses from anilines and carbonyl compounds, as well as metal-catalyzed dehydrogenative cyclization and other “greener” methods [ 14 , 15 , 16 , 17 ]. In the current work, quinolines 5a – 5f , 6a – 6f and 7a – 7g were synthesized using the Friedländer method by condensation of the corresponding 2-aminobenzaldehydes, prepared from substituted 2-nitrobenzaldehydes [ 18 ], with aldehydes or ketones.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, following pharmaceutical green chemistry principles, which seek to eliminate unnecessary environmental impact, but deliver efficiently life-saving medicines, each synthesis including quinoline synthesis, must strive for the right choice of starting material, ideal number and order of chemical steps, the suitable use of solvents and reagents, and effective strategies for isolation and purication. 34,35 Moreover, sometimes there are not available green methods for the preparation of active antitrypanosomal quinoline molecules, but in general, the developments in the quinoline chemistry towards new antiparasitic quinoline agents must harmonize the classical syntheses offering higher efficacy, promptness and a greater orientation to molecular diversication.…”
Section: Classical and Contemporary Approaches To Quinolines Synthesismentioning
confidence: 99%
“…Quinoline derivatives, an important class of nitrogenbased heterocycles with remarkable biological activities, have attracted attention of the synthetic organic chemists over the past years. 93,94 Recently, Shahabi and Tavakol 95 showed that the reaction of anilines with aromatic and enolizable aldehydes, catalyzed by ChCl/SnCl 2 (1:2), can efficiently furnish trisubstituted quinolines (13) in good to excellent yields and mild conditions (Scheme 12).…”
Section: Mcr Based On Nucleophilic Addition To Imines or Enaminesmentioning
confidence: 99%